Equidade e descentralização: os mitos do SUS - Souza, Maria Isabel Ferreira de (1997)
The Unique System Health (SUS) was shaped to be an instrument of social justice, using the strategy of decentralization Politico-Administrative, according to the equity, universalization and integrity of the health actions. In the me anti me. after eight years of approval and constitutional legitimation, the implantation proceeding has resigned deflexions during the tragectory idealized by the Sanitarian Reíorm. In this dissertation will be íocalized the possible causes 01' the SUS misguiding obstacles, pointing out two conceiving questions: The equity and the health services decentralization. The great interrogation that permeates alI the work is through the questioning about the SUS possibility, while a theoretical model, realized in Utopian casts, passible to be transformed in more one myth of the brazilian social imaginary, than an effective Political-social, turned to the acquisition of a participating and democratical society.